2022
DOI: 10.3390/ijerph19095776
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Burnout among Teachers: A Systematic Review of Longitudinal Studies

Abstract: We aimed to review the determinants of burnout onset in teachers. The study was conducted according to the PROSPERO protocol CRD42018105901, with a focus on teachers. We performed a literature search from 1990 to 2021 in three databases: MEDLINE, PsycINFO, and Embase. We included longitudinal studies assessing burnout as a dependent variable, with a sample of at least 50 teachers. We summarized studies by the types of determinant and used the MEVORECH tool for a risk of bias assessment (RBA). The quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 133 publications
(305 reference statements)
2
8
0
2
Order By: Relevance
“…This study also showed that there is a significant negative correlation between job satisfaction and teacher burnout. The finding is in consistence with a systematic review of longitudinal studies on determinants of teacher burnout,which found that job satisfaction was the most predictive factor (42). As a positive attitude related to job, job satisfaction can significantly negatively predict teacher burnout (43).…”
Section: Discussionsupporting
confidence: 75%
“…This study also showed that there is a significant negative correlation between job satisfaction and teacher burnout. The finding is in consistence with a systematic review of longitudinal studies on determinants of teacher burnout,which found that job satisfaction was the most predictive factor (42). As a positive attitude related to job, job satisfaction can significantly negatively predict teacher burnout (43).…”
Section: Discussionsupporting
confidence: 75%
“…The use of stepwise regression, although an intuitive and interesting approach when dealing with several samples and numerous potential determinants, requires caution in interpretation [ 56 ]. In addition, we were not able to consider all potential wellbeing determinants and possible interaction effects (those implying personality traits or emotion regulation strategies) even though they may play an important role in the process [ 26 , 37 , 73 , 74 ]. Moreover, information on certain categories of teachers or education staff is lacking (e.g., university teachers or school support staff).…”
Section: Discussionmentioning
confidence: 99%
“…It will allow us to delve further into the subject, confirm or refute the associations presently highlighted, and evaluate trends. To decisively strengthen the body of evidence, longitudinal and intervention studies would also be crucial [ 20 , 37 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations